Pengaruh Pemutihan, E-Samsat, dan Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Ni Nyoman Alit Putri Sunariani; Rai Dwi Andayani W (UNHI Press, 2026)
Taxes are a crucial source of state revenue supporting economic growth and development, including at the regional level. Motor vehicle taxes, as part of regional taxes, contribute significantly to Regional Original Income (PAD), which is then used to finance various development programs and public services. However, the level of compliance with vehicle tax obligations remains a challenge faced by local governments, including in Gianyar Regency. This study examines the effect of the tax amnesty program, e-Samsat services, and the drive-thru Samsat system on motor vehicle taxpayer compliance. This study used a quantitative method with an associative approach. The study population was all motorized vehicles registered with the Gianyar Samsat in 2024. The sample size was 100 respondents, calculated using the Slovin formula and an accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results showed that the tax amnesty program and e-Samsat services had a positive and significant effect on motor vehicle taxpayer compliance. Meanwhile, the Samsat Drive-Thru system had no significant effect on taxpayer compliance.